Discharge stability analysis of top discharge blow tank in dense-phase pneumatic conveying system. (2nd January 2022) - Xu, Guiling; Zhang, Qi; Chen, Feihan
Abstract: Dense-phase pneumatic conveying is widely applied in large-scale entrained-bed gasification systems for feeding and conveying pulverized coal into the gasifiers. The discharge stability of blow tanks will affect the conveying process of powders in the conveying pipelines, and ultimately influence the long-term safe and stable operation of the gasifiers. In this paper, aiming at the problem of controllable discharge and conveying of powders in dense-phase pneumatic conveying systems, the research on the discharge analysis of a top discharge blow tank was carried out, which improves the understanding of top discharge blow tanks. Shannon entropy analysis and relative standard deviation analysis based on instantaneous solid mass flow rate signals were used as indicators for the discharge stability. The effects of operating conditions, powder external moisture content, and blow tank structural parameters on the discharge stability of a top discharge blow tank were investigated. The results indicate that for a given pneumatic conveying system, there exists an optimal supplementary gas volume flow rate corresponding to the most stable discharge process of the blow tank. With an increase in the external moisture content of pulverized coal, the discharge stability of the blow tank first increases and then decreases. As the riser diameter increases, the discharge process of the blow tank becomes unstable owing to the increase in the randomness of the conveying process.